2000
DOI: 10.1103/physrevb.62.2624
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the Aharonov-Bohm oscillations and the energy spectrum in a single-mode ballistic ring

Abstract: The temperature dependence of the amplitude of the Aharonov-Bohm ͑AB͒ oscillations in a single mode ballistic ring has been measured. The experimental data is analyzed using the exact energy spectrum of an ideal ring with a finite width and the Landauer-Büttiker formula to calculate the conductance of the ring. We show that the temperature dependence of the AB oscillations can be explained in terms of the thermally averaged transmission probability through the energy levels of the ring provided the additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…21 At low temperatures, coherence in ballistic conductors is limited mainly by electron-electron scattering 22 and thermal averaging. 16,17,23 Additionally, decoherence due to charge fluctuations has been suggested 21 and discussed to evoke a measurement-configuration dependence of dephasing with temperature. 20 Recently, a strong configuration dependence has been observed in a symmetric AB ring with finger top gates ͑tg͒.…”
Section: Introductionmentioning
confidence: 98%
“…21 At low temperatures, coherence in ballistic conductors is limited mainly by electron-electron scattering 22 and thermal averaging. 16,17,23 Additionally, decoherence due to charge fluctuations has been suggested 21 and discussed to evoke a measurement-configuration dependence of dephasing with temperature. 20 Recently, a strong configuration dependence has been observed in a symmetric AB ring with finger top gates ͑tg͒.…”
Section: Introductionmentioning
confidence: 98%
“…14,15 A number of experiments have measured the dephasing rate in ballistic quantum dots [16][17][18][19][20] and rings. [21][22][23][24] The dephasing rate is extracted from the temperature ͑T͒ dependence of the AB oscillation amplitude. For ballistic rings, it is found that the AB amplitude ⌬R AB decrease with T according to the relationship ⌬R AB ϰ exp͑− L / ͑T͒͒.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a dc driving voltage, these frequencies cast dc currents from 0.1 nA to a few nA. These currents are small but within the range observed in experiments on Aharanov-Bohm rings (see 3,[43][44][45][46].…”
Section: Discussionmentioning
confidence: 79%
“…In experiments, the rings have typical diameters ranging from some hundreds of nm to a few μm, and have a mean level spacing ∼ 0.5 meV. 44 In arrays of rings, the typical level spacing is estimated to be smaller ∼ 0.001 meV. 45 This corresponds to resonant frequencies / h ∼ 1-500 GHz.…”
Section: Discussionmentioning
confidence: 99%